PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PADA BADAN PENGELOLAAN KEUANGAN DAERAH PEMERINTAH PROVINSI SULAWESI SELATAN - Widya Ramlah (AkMen JURNAL ILMIAH, 2019)
This Research aims to : (1) knowing the effect of governmental accounting standards for quality of financial report in regional financial management agency south sulawesi. (2) knowing the effect of internal control systemforquality of financial report in regional financial management agency south sulawesi. (3) knowing the effect of governmental accounting standards and internal control systemforquality of financial report in regional financial management agency south Sulawesi. The data used are primary data. All data in this study collected by using questioner. Questioner given away to90aparatur in regional financial management agency south sulawesi. Data were analyzed using path analysis using SPSS for windows version 23.00.The result of research indicate that variable of : governmental accounting standards and internal control system simultaneustly and partially have positif and signifikanforquality of financial report in regional financial management agency south sulawesi.